2013
DOI: 10.1186/1752-153x-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and assessment of potential environmental risk of tailings stored in seven impoundments in the Aries river basin, Western Romania

Abstract: BackgroundThe objective of this study was to examine the potential environmental risk of tailings resulted after precious and base metal ores processing, stored in seven impoundments located in the Aries river basin, Romania. The tailings were characterized by mineralogical and elemental composition, contamination indices, acid rock drainage generation potential and water leachability of hazardous/priority hazardous metals and ions. Multivariate statistical methods were used for data interpretation.ResultsTail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
(31 reference statements)
0
23
1
Order By: Relevance
“…The second PC with 22 % of total variance was correlated with the natural input of Pb (moderate influence), as shown by the positive loadings with alkaline and alkaline earth elements of geogenic origin. 39 This shows the greater influence of the anthropogenic origin of As from the right-bank tributaries compared with the natural source of the left-side tributaries on the sediments in the main stream. The most probable source of Zn was the Abrud River, as shown above.…”
Section: Multivariate Statisticsmentioning
confidence: 93%
See 1 more Smart Citation
“…The second PC with 22 % of total variance was correlated with the natural input of Pb (moderate influence), as shown by the positive loadings with alkaline and alkaline earth elements of geogenic origin. 39 This shows the greater influence of the anthropogenic origin of As from the right-bank tributaries compared with the natural source of the left-side tributaries on the sediments in the main stream. The most probable source of Zn was the Abrud River, as shown above.…”
Section: Multivariate Statisticsmentioning
confidence: 93%
“…[35][36][37] These techniques can be used to obtain relationships between parameters and sampling sites, or to identify the important factors and sources influencing sediment quality. 39 HCA and LDA were used to group the sediments (sites) in relation to their degree of metal contamination. A previous study revealed that tailings deposited in the Aries River Basin pose high contamination risk for the sediments, especially by As, Cd, Cu and Pb.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The I geo , originally defined by Müller (1969), has been used to evaluate the pollution level of PTEs in soils (Loska et al 2004), sediments (Shafie et al 2013), and tailings (Levei et al 2013). It can be calculated using: Igeo=italiclog2(Cnormaln/1.5Bnormaln) where C n is the measured concentration of the metal ions in soil, B n is the geochemical background value (local baseline) of the corresponding metal, and the coefficient 1.5 is used to detect very small anthropogenic influences (Müller 1969).…”
Section: Methodsmentioning
confidence: 99%
“…However, this inventory of risks only includes the aspects determined or influenced by the mining activities, while a complex analysis of the risks induced to mining settlements should also consider the typology of additional risks. Despite the existence of several other papers where social, economic, and environmental risks as pertaining to the mining areas of the Apuseni Mountains have been previously studied (Surd et al, 2007;Muntean and Constantin, 2009;Ş tefȃ nescu et al, 2011Levei et al, 2011Levei et al, , 2013Moldovan et al, 2013;Ozunu et al, 2009;Forray, 2002;Forray and Hallbauer, 2000;Florea et al, 2005;Bird et al, 2005;Costan et al, 2010), this paper is unique in its approach to addressing such limitation. Thus, the study pursues to achieve a complex image of vulnerability of mining settlements taking into account their dynamics and evolution.…”
Section: Data Collectionmentioning
confidence: 72%